Efektivitas Pengelolaan Pembelajaran Inklusi di Sekolah Dasar Non-SDLB - Daniar Asyari; Jennisa Tasya Kamila; Kaamilah Nurnanzhiifa; Linda Cibya Rahmawati; Maharani Sartika Dewi (Journal on Education, 2023)
Children with Special Needs (ABK) is another term used besides the word "Extraordinary Children" which indicates that the child has a special disorder. They have different characteristics from one child to another. This is what makes Children with Special Needs need special education services where these services adapt to their abilities and potential. A teacher or prospective educator for ABK is required to have high patience, as well as physically and mentally working well. In addition, the selection and design of learning methods must be considered in accordance with inclusive education standards so that children with special needs can participate in learning activities properly. In this study, we will discuss how to design learning methods for children with special needs who generally learn together in inclusive classes.